2018
DOI: 10.3389/fnins.2018.00834
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endogenous Neuroprotective Mechanisms in the Prevention of Retinal Ganglion Cells Degeneration

Abstract: Retinal neurons are not able to undergo spontaneous regeneration in response to damage. A variety of stressors, i.e., UV radiation, high temperature, ischemia, allergens, and others, induce reactive oxygen species production, resulting in consecutive alteration of stress-response gene expression and finally can lead to cell apoptosis. Neurons have developed their own endogenous cellular protective systems. Some of them are preventing cell death and others are allowing functional recovery after injury. The high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 280 publications
(310 reference statements)
2
46
0
1
Order By: Relevance
“…The significant role of Bax which is a pro‐apoptotic protein for glaucoma formation was reported in previous studies . Libby et al carried out a study on mice with DBA/2J Bax ablation and revealed that Bax was a significant factor in RGC death, that Bax ablation prevented apoptosis in RGC, and that Bax ablation decelerated axonal death even though there is no Bax‐associated apoptosis .…”
Section: Discussionmentioning
confidence: 90%
“…The significant role of Bax which is a pro‐apoptotic protein for glaucoma formation was reported in previous studies . Libby et al carried out a study on mice with DBA/2J Bax ablation and revealed that Bax was a significant factor in RGC death, that Bax ablation prevented apoptosis in RGC, and that Bax ablation decelerated axonal death even though there is no Bax‐associated apoptosis .…”
Section: Discussionmentioning
confidence: 90%
“…As BDNF may trigger a wide variety of neutroprotective mechanisms, we may hypothesize that BDNF may benefit the glaucoma course by acting as anti-apoptotic, as well as anti-autophagic molecule, to strengthen cell survival. In this context, the fatty acid amide hydrolase inhibitors and endocannabinoid system were investigated as glaucoma neuroprotectans [72]. An interesting review [73] focused on endogenous neuroprotective factors involved in RGCs survival, covering new therapeutic strategies, as the ones suggested herein.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophic factors generally include the neurotrophin family: NGF, BDNF, neurotrophin-3 (NT-3) and neurotrophin-4/5 (NT-4/5); the glial cell-line derived neurotrophic factor (GDNF) family: GDNF, neurturin (NRTN), artemin (ARTN), and persephin (PSPN); and CNTF [80,81]. It was reported that most of these neurotrophic factors, which can be produced by glial cells, increase RGC survival in different experimental models of injury [53,[82][83][84][85][86][87][88]. Neurotrophic factors bind to different receptors and transduce diverse intracellular signals.…”
Section: Neurotrophic Factorsmentioning
confidence: 99%
“…It was reported that most of these neurotrophic factors, which can be produced by glial cells, increase RGC survival in different experimental models of injury [53,[82][83][84][85][86][87][88]. Neurotrophic factors bind to different receptors and transduce diverse intracellular signals.…”
Section: Neurotrophic Factorsmentioning
confidence: 99%